TOTAL PHENOLIC CONTENT AND "IN-VITRO" ANTIOXIDANT ASSAY OF TWO MEDICINAL RICE VARIETIES - KARUNGKAVUNI AND KUZHIADICHAN. - K.KRISHNANUNNI; DR.SUDHA RAMAIAH; DR.ANAND ANBARASU (International Journal of Pharma and Bio Sciences, 2014)
The objective of this study is to investigate the total phenolic content and the antioxidant activity of two medicinal rice varieties of India “Kuzhiadichan” and “Karungkavuni”. Total phenolic content (TPC) was estimated using Folin Ciocalteu colorimetric method, antioxidant assay was done using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay and ferric reducing antioxidant power (FRAP) assay. Phenols were found to be present in both the rice varieties. Both rice varieties also showed antioxidant activity in DPPH assay and FRAP assay, the IC 50 value of the rice varieties were 46.98 µg/ml and 28.01 µg/ml for “Kuzhiadichan” and “Karungkavuni” varieties respectively. The correlation coefficient and regression analysis of total phenolic content with DPPH assay and FRAP assay showed significant positive correlation coefficient values and coefficient of regression values.